Enhancing Medical Decision-Making Evaluations: Introduction of Normative Data for the Capacity to Consent to Treatment Instrument. (April 2016) - Gerstenecker, Adam; Niccolai, Lindsay; Marson, Daniel; Triebel, Kristen L.
A number of measures have been developed to assess medical decision-making capacity (MDC) in adults. However, their clinical utility is limited by a lack of available normative data. In the current study, we introduce age-independent and age-adjusted normative data for a measure of MDC: the Capacity to Consent to Treatment Instrument. The sample consisted of 308 cognitively normal, community-dwelling adults ranging in age from 19 to 86 years. For age-adjusted norms, individual raw scores were first converted to age-corrected scaled scores based on position within a cumulative frequency distribution and then grouped according to empirically supported age ranges. For age-independent norms, the same method was utilized but without age-corrections being applied or participants being grouped into age ranges. This study has the potential to enhance MDC evaluations by allowing clinicians to compare a patient's performance on the Capacity to Consent to Treatment Instrument with that of adults regardless of age as well as to same age peers. Tables containing normative corrections are supplementary material available online athttp://asm.sagepub.com/supplemental .